Perbandingan Rasio Neutrofil Terhadap Limfosit pada Pasien Angina Pektoris Stabil, Angina Pektoris Tidak Stabil, dan Infark Miokard Akut Non-Elevasi Segmen St di RSUP Prof. Dr. R. D. Kandou Manado - Ari, Teguh Putra Anta; Wantania, Frans Erwin Nicolaas; Rotty, Linda Wilhelma Ancella (Green Publisher Indonesia, 2025)
Background: Coronary artery disease (CAD) progresses from stable atherosclerotic plaque to unstable plaque rupture, resulting in unstable angina (UA) and non–ST-elevation myocardial infarction (NSTEMI). Inflammation plays a pivotal role in this continuum, and the neutrophil-to-lymphocyte ratio (NLR) has emerged as a potential inflammatory biomarker. However, local data comparing NLR across the clinical spectrum of stable angina pectoris (SAP), UA, and NSTEMI remain limited. Purpose: To compare NLR values among patients with SAP, UA, and NSTEMI at Prof. Dr. R. D. Kandou Hospital Manado. Methods: This analytic comparative study used a cross-sectional design with secondary data from medical records of SAP, UA, and NSTEMI patients (January–July 2025). Total sampling was employed. NLR was obtained from complete blood count at admission. Data distribution was assessed using the Shapiro–Wilk test. Kruskal–Wallis and Mann–Whitney tests were used to compare NLR among groups. Results: A total of 261 subjects were included: 124 SAP, 80 UA, and 57 NSTEMI. Mean NLR increased progressively from SAP (2.15 ± 0.91) to UA (3.10 ± 2.03) and NSTEMI (6.50 ± 7.84). NLR was non-normally distributed in all groups (p < 0.05). There were significant differences in NLR across the three diagnoses (p = 0.000). Post-hoc analysis showed significant pairwise differences between SAP–UA, SAP–NSTEMI, and UA–NSTEMI (all p = 0.000). Conclusion: There is a significant difference in NLR among SAP, UA, and NSTEMI, with higher values corresponding to increased clinical severity.